The role of urban development tools in new “Cities Fabrication” applications (Damascus University Journal for engineering sciences, 2021)
The concept of "Cities fabrication" is a spatial requirement as it reflects the development of cities, organizes their dynamics and integrates them into contemporary contexts. The principals and issues of sustainable development are the main tools in the formulation of urban fabrics. The sustainable urban project and the characteristics of its applications appears as an important factor in reshaping cities, by adapting the pillars of sustainable project and the matrix of spatial approaches and projections.  The problematic of Damascus city is known within the actual context by the difficulty of understanding its spatial relationships, and the failure to adopt the correct urban fabric for its big challenges, and thus to develop its new fabrication for the coming period of reconstruction.  The research aims to understand and analyze the concept of new cities fabrication and show methodologies and references that affect the development of urban fabrics within the applications of sustainable urban project tools. It is relevant to reach the identification of spatial considerations and requirements, to conduct the exploration of the new urban context of the city of Damascus.
Keywords: urban industry; sustainable urban project; spatial matrix; urban fabric